Evaluation of CHROMagar™ LIN-R for the Screening of Linezolid Resistant Staphylococci from Positive Blood Cultures and Nasal Swab Screening Samples - Delphine Girlich; Liliana Mihaila; Vincent Cattoir; Frédéric Laurent; Christine Begasse; Florence David; Carole-Ann Metro; Laurent Dortet (MDPI AG, 2022)
The increasing number of nosocomial pathogens with resistances towards last resort antibiotics, like linezolid for gram positive bacteria, leads to a pressing need for screening and, consequently, suitable screening media. Some national guidelines on infection prevention (e.g., in Germany) have already recommended screening for linezolid-resistant bacteria, despite an accurate screening medium that was not available yet. In this study, we analyzed the performance and reliability of the first commercial chromogenic medium, CHOMagar™ LIN-R, for screening of linezolid-resistant gram-positive isolates. Thirty-four pure bacterial cultures, 18 positive blood cultures, and 358 nasal swab screening samples were tested. This medium efficiently detected linezolid-resistant S. epidermidis isolates from pure bacterial cultures and from positive blood cultures with a high sensitivity (100%) and specificity (100%). Among the 358 nasal swab screening samples prospectively tested, 10.9% were cultured with linezolid-resistant isolates (mostly S. epidermidis). Of note, slight growth was observed for 7.5% samples with linezolid-susceptible isolates of S. epidermidis (n = 1), S. aureus (n = 1), Enterococcus faecalis (n = 4), Lactobacillus spp. (n = 3), gram negatives (n = 18). Moreover, few Candida spp. also cultured on this medium (1.4%).